Water Processing for Isotope Recovery Using Porous Zero Valent Iron. (2nd January 2020) - Larsen, George; Hunyadi Murph, Simona E.; Coopersmith, Kaitlin; Mitchell, Lucas
Abstract: Reduction-oxidation cycles of metals can be harnessed to create a reusable tritiated water processing system. The concept is straightforward; a tritium-contaminated steam passes over a hot metal bed converting the metal to a metal oxide and liberating hydrogen isotopes for further processing and isotope separation. The bed is regenerated by converting the metal oxide back to a bare metal using protium gas, creating a clean water stream. Free oxygen is not produced during the cyclical process, making it safe for use in a hydrogen processing facility, and the only by-product is detritiated water. Porous zero valent iron (p-ZVI) has been identified as an ideal candidate material for this process due to its low cost, unique morphology, and favorable thermodynamics. Therefore, investigations of p-ZVI were conducted to better understand how a bed composed of such material would behave in a tritium processing facility. The thermal and physical properties were assessed, along with cycling and isotope effects. The results indicate that p-ZVI beds could serve as a low-cost, reusable system for the treatment of water in tritium processing facilities.